Milk cortisol response to group relocation in lactating cows. Issue 1 (2nd March 2017) - Pošćić, Nataliya; Gabai, Gianfranco; Stefanon, Bruno; Da Dalt, Laura; Sgorlon, Sandy
Abstract : The aim of the study reported in this Research Communication was to analyse the variations of milk cortisol concentrations in response to the relocation of dairy cows between production groups. Milk cortisol measured during 3 consecutive days did not vary significantly in cows without environmental perturbation. However, relocation of cows caused a significant increase of cortisol in milk starting from the first milking after the group change. This suggests that cortisol in milk can be a suitable biomarker to assess the HPA response of dairy cows to a short/medium-term environmental challenge.